Gestão da segurança da informação: certificação digital - Ramiro, Marcelo Lepsch (2008)
More over, the information has become the main asset of the institutions. Being thus, the Information Security (IS) is getting attention as one of the activities of extreme importance in the corporations. Guarantee the confidentiality, integrity, availability, no deny and legality becomes something very important for the day-by-day of the businesses. An analysis of the risk, passing through the assessment of the threats and vulnerabilities, is mandatory to let grow the activities of the institutions. Digital Certification came into IS to guarantee the Not Deny (ND) because it makes the unquestioned identification of the person that makes the action. Therefore, Information Security can be defined as a knowledge field focused in the protection of the information assets against: unauthorized access, improper modifications, not availability, deny of authorship and illegality.